Creative competence in borrowings : words of Japanese origin in Slovene - Chikako Shigemori Bučar (Linguistica, 2011)
Japanese has no category of gender or number. Nouns as well as adjectives have no inflection. The phonological construction of words is syllabic and there is no stress accent but pitch accent. Five vowels have short and long opposition. On the other hand, Slovene has categories of number and gender. Nouns are inflected according to six cases. Phonologically, all nouns carry a stress accent. In this paper, the gender and number assignment to loanwords of Japanese origin in Slovene is discussed on the basis of the morphology and phonology of the source and recipient languages. Assignment rules have certain morphological and semantic foundations. The relative competence of the speakers of the recipient language, Slovene, is particularly noticeable when activating the categories and rules that are specific to their own language. The integration of loanwords may be observed through the additional derivation of adjectives and nouns within the framework of the recipient language.